Implementasi Model Pembelajaran Kuantum untuk Meningkatkan Sikap Percaya Diri dan Hasil Belajar Siswa - Thomas Yuli Padmara; Agnes Herlina Dwi Hadiyanti; Albertus Saptoro (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
The aims of this study are as follows:(1) To describe efforts to increase self-confidence and student learning outcomes through the use of a quantum learning model, (2) To increase student confidence through the use of quantum learning models (3) To improve student learning outcomes through the use of quantum learning models. This research is Classroom Action Research consisting of two cycles: planning, implementing, observing, and reflecting. The data analysis technique used is a quantitative analysis and qualitative analysis which the data collection techniques used were interviews, observations, and tests. The subjects of this study were 20 students in third grade of Kanisius Demangan Baru of Elementary School. The results showed: (1) efforts to increase self-confidence and student learning outcomes by applying quantum learning through growth stages; natural; name; describe; repeat; and celebrate, (2) the application of quantum learning models can increase students' self-confidence; from the starting condition, the students' self-confidence was 51% increased to 70% in the first cycle, and increased to 92% in the second cycle, (3) the application of the quantum learning model can improve student learning outcomes; from the mean value of the starting conditions of 78.05; increased to 83.5 in cycle I, and increased to 90.5 in cycle II.